(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This scientific article examines new trends in the field of translation studies. The study provides an analysis of contemporary methodological approaches to translation studies, as well as practical examples of applying new technologies and tools in the field of translation. The research results will help to understand the influence of digitization, cultural changes, and technological innovations on the development of translation studies.